Alternative proteins in the human diet: Meta-Analytical analyses from 2014 to 2024 - Siqueira , Paloma Danielle Brito; Sanglard, Demerson Arruda; Pereira, Sidney; Antunes, Maria Fernanda Lousada; Silva, Leonardo Máximo; Nogueira, Ariane da Silva; Silveira, Ana Carolina Ataíde; Torres, Brenda Franciny; Batista, Flávia Echila Ribeiro (Brazilian Journal of Production Engineering, 2025)
This work details the evolution of the use of alternative proteins in human diets, based on a meta-analytical review from 2014 to 2024, highlighting technological advances, cultural challenges, and environmental impacts. Plant-based proteins lead in accessibility, reflecting cultural familiarity, affordability, and sustainability. Microalgae and fungi have also progressed, offering healthy nutritional benefits despite higher costs. Insects have been gaining ground, especially in Asia and Africa, but face resistance in the West. Agro-industrial residues are emerging as a sustainable option, standing out in the context of the circular economy. Globally, microalgae lead in nutritional benefits, while plants and seafood stand out for health and accessibility. Environmental impacts vary plants and insects have low emission levels, while microalgae and seafood face challenges due to high production costs. Nutritional efficiency is highest in plants and microalgae, while insects and agro-industrial residues show potential in specific niches. The alternative protein market is growing, driven by an increase in companies and patents, particularly in Asia and Europe. Despite regional disparities, the trends reflect a shift toward more sustainable and alternative diets. To consolidate these sources, public policies, technological innovations, and food education strategies are essential. Thus, alternative proteins can increasingly become viable in addressing global food security and sustainability challenges.